Etimologi nama dan makna Labuan (Sabah) berdasarkan konsep linguistik perbandingan - Raja Ariffin, Raja Masittah (Universiti Putra Malaysia Press, 2014)
The word etymology originated from the old Greek language which means “to find the truth”. Scholars defined etymology as a study of word origins, and the way in which their meaning have changed throughout history. Malay language belongs to the Austronesian language family and more than 1000 Austronesian languages are scattered from Taiwan in the north and portions of mainland Southeast Asia to Madagascar in the west, New Zealand in the southwest and the Easter Island in the southeast. Malay also belongs to the Western Malayo-Polynesian branch of the Austronesian language family which includes Borneo, Sumatera, Java, Sulawesi, and others. Labuan is one of the federal government territories which is located off the coast of the state of Sabah. Thus, the objective of this study is to trace the history of how the name Labuan in Sabah being derived. Data were collected by means of structural interviews with historian in Labuan, and the questions were orally asked and the responses were recorded through the written mode. This study utilised qualitative approach and the data analysed was based on comparative linguistic concept of cognate languages. The findings revealed that the name Labuan derived from the Malay word labuhan means harbour. It appears that the word labuan from the the Malay basic word labuh almost certainly is a native Malay word, not loans from Dutch or any other western languages.